A national report of nursing home information technology: year 1 results. (23rd April 2016) - Alexander, Gregory L; Madsen, Richard W; Miller, Erin L; Schaumberg, Melissa K; Holm, Allison E; Alexander, Rachel L; Wise, Keely K; Dougherty, Michelle L; Gugerty, Brian
Abstract: Objective: To provide a report on year 1 results of a national study investigating nursing home information technology (IT) adoption, called IT sophistication. Methods: A reliable and valid survey was used to measure IT sophistication. The target goal was 10% from each state in the United States, 1570 nursing homes. A random sample of homes from each state was recruited from Nursing Home Compare. Results: The team reached 2627 nursing home administrators, among whom 1799 administrators agreed to participate and were sent a survey. A total of 815 surveys were completed (45.3% response rate), which was below the goal. Facilities in the participating sample have similar demographic characteristics (ownership, total population in a location, and bed size) to the remaining homes not participating. There are greater IT capabilities in resident care and administrative activities, less in clinical support. The extent of use of these capabilities appears to be highest in administrative activities and lowest in clinical support. IT in resident care appears to be the most integrated with internal and external stakeholders. IT capabilities appear to be greater than IT extent of use in all health domains, with the greatest difference in resident care. Discussion: National evaluations of nursing home IT are rare. Measuring trends in IT adoption in a nationally representative sample provides meaningful analytics that could be more useful for policy makers and nursing home leaders in the future. Conclusion: Discovering national baseline assessments is a first step toward recognizing nursing home trends in IT adoption.